PERAN LURAH DALAM PEMBERDAYAAN MASYARAKAT DI KELURAHAN BALOCCI BARU - MURYAM, MURYAM; Septiani, Indri (Patria Artha Management Journal, 2023)
This study aims to determine the role of the lurah in community empowerment in Balocci Baru Village, Balocci District, Pangk ep Regency, the obstacles and efforts tak en by the Lurah in community empowerment in Balocci Baru Village, Balocci District, Pangkep Regency. Respondents in this study were 48 people consisting of all staff of Balocci Baru Village, Balocci District, Pangk ep Regency plus community leaders consisting of traditional leaders, religious leaders, youth leaders, educators and women leaders, RWand RT heads as well as chairmen and members of LPM. descriptive analysis technique method supported by quantitative data. The results showed that 1. The role of the lurah in community empowerment as a motivator, facilitator and motivator in Balocci Baru Village, Balocci Distr ict, Pangkep Regency as a whole with an average score of 2.92 or was in the good category. 2. Obstacles faced by the lurah in community empowerment in Balocci Baru Village, Balocci District, Pangk ep Regency, include: a). Lack of community participation in community empowerment; b) Lack of public k nowledgeabout the importance of community empowerment; c) Lack of community cooperation. 3. Efforts tak en by the lurah in community empowerment in Balocci Baru Village, Balocci District, Pangkep Regency.